The Paradox of Deliberation Jürgen Habermas and the Rational Approach to the Normative Theory of Democracy - Parcon, Ian Clark R. (2022)
Jürgen Habermas anchors his theory of democracy on communicative rationality, which he translates into procedural rationality geared towards the attainment of consensus. In this study, I present his theory of democracy and discuss its limitations. I then argue that for a more comprehensive theory of democracy, the insights from other theories, specifically, the agonistic perspective of Chantal Mouffe, should be seriously taken into account.
Keywords: Habermas, Jurgen; Democracy; Discourse analysis